Modelling of crystalline C-60 EEL spectra - Nicholls, R; Nguyen-Manh, D; Cockayne, W (2006)
Electron energy-loss spectra are simulated from two experimentally determined C. crystal structures. It is found that the decrease in symmetry from an face centred cubic to a simple cubic structure cause a splitting of the unoccupied states resulting in a splitting and broadening of the peaks in the spectrum and a change in the relative heights of those peaks. The simulated spectra are then compared to experimental spectra from C. thin films and nanocrystals.